Myalgic Encephalomyelitis/Chronic Fatigue Syndrome Diagnosis and Management in Young People: A Primer - Rowe, Peter C.; Underhill, Rosemary A.; Friedman, Kenneth J.; Gurwitt, Alan; Medow, Marvin S.; Schwartz, Malcolm S.; Speight, Nigel; Stewart, Julian M.; Vallings, Rosamund; Rowe, Katherine S. (Frontiers in Pediatrics, 2017)
Myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) is a complex disease that affects children and adolescents as well as adults. The etiology has not been established. While many pediatricians and other healthcare providers are aware of ME/CFS, they often lack essential knowledge that is necessary for diagnosis and treatment. Many young patients experience symptoms for years before receiving a diagnosis. This Primer, written by the International Writing Group for Pediatric ME/CFS provides information necessary to understand, diagnose, and man-age the symptoms of ME/CFS in children and adolescents. ME/CFS is characterized by overwhelming fatigue with a substantial loss of physical and mental stamina. Cardinal features are malaise and a worsening of symptoms following minimal physical or mental exertion. These post-exertional symptoms can persist for hours, days, or weeks and are not relieved by rest or sleep. Other symptoms include cognitive problems, unrefreshing or disturbed sleep, generalized or localized pain, light-headedness and additional symptoms in multiple organ systems. While some young patients can attend school, on a full or part-time basis, many others are wheelchair dependent, housebound, or bedbound. Prevalence estimates for pediatric ME/CFS vary from 0.1%-0.5%. Because there is no diagnostic test for ME/CFS, diagnosis is purely clinical, based on the history and the exclusion of other fatiguing illnesses by physical examination and medical testing. Co-existing medical conditions including orthostatic intolerance are common. Successful management is based on determining the optimum balance of rest and activity to help prevent post-exertional symptom worsening. Medications are helpful to treat pain, insomnia, orthostatic intolerance and other symptoms. The published literature on ME/CFS and specifically that describing the diagnosis and management of pediatric ME/CFS is very limited. Where published studies are lacking, recommendations are based on the clinical observations and practices of the authors.